2021
DOI: 10.1177/00034894211028489
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Obstructive Sleep Apnea and Pediatric Obesity: A Nationwide Analysis

Abstract: Objective: Pediatric obstructive sleep apnea (OSA) can have both acute and chronic consequences when untreated. We hypothesize that a link exists between childhood obesity and OSA at nationwide level, with race, gender, and socioeconomic status conferring their own risk for pediatric OSA. Methods: This study examined nationwide discharges in 2016 using the Kids’ Inpatient Database (KID). The International Classification of Diseases, 10th revision, Clinical Modification (ICD-10-CM) codes for obesity (E66.0) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
(31 reference statements)
2
13
1
Order By: Relevance
“…While some reports have found obesity to be independently related to the risk of OSAS ( 15 , 16 ), this finding was not replicated in the present study, and the relevance of these risk factors remains controversial. However, this study revealed a relationship between obesity and OSAS severity, suggesting that obesity may play a role in the increased risk of OSAS as reported by Bachrach et al ( 15 ). While obese individuals may not exhibit OSAS, obesity can nonetheless contribute to pre-vertebral soft tissue hyperplasia of the upper airway, pharyngeal airway stenosis, and increased airway closure resistance, aggravating extant OSAS.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While some reports have found obesity to be independently related to the risk of OSAS ( 15 , 16 ), this finding was not replicated in the present study, and the relevance of these risk factors remains controversial. However, this study revealed a relationship between obesity and OSAS severity, suggesting that obesity may play a role in the increased risk of OSAS as reported by Bachrach et al ( 15 ). While obese individuals may not exhibit OSAS, obesity can nonetheless contribute to pre-vertebral soft tissue hyperplasia of the upper airway, pharyngeal airway stenosis, and increased airway closure resistance, aggravating extant OSAS.…”
Section: Discussioncontrasting
confidence: 99%
“…Efforts to identify OSAS-related risk factors at an early time point are essential to improving patient outcomes. In prior reports, tonsillar hypertrophy and adenoid hypertrophy ( 7 , 10 , 11 ), as well as obesity ( 8 , 15 ), were identified as critical factors associated with the development of OSAS in children. Other risk factors including asthma ( 16 ), pre-term birth ( 17 , 18 ), being male ( 11 ), parental smoking ( 19 , 20 ), habitual snoring ( 21 ), and ethnicity ( 22 ) have also been reported to be associated with OSAS incidence, but these findings are somewhat controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional metabolic markers have been assessed, given the increasing rates of pediatric obesity (Childhood Obesity Facts, 2022), and concomitant obesity in children with OSA (Bachrach et al, 2022). Comorbid diagnoses to obesity, such as insulin resistance and dyslipidemia, have been evaluated in pediatric OSA (Deboer et al, 2012;Zong et al, 2013;Bhushan et al, 2014;Amini et al, 2017;Siriwat et al, 2020).…”
Section: Biomarkersmentioning
confidence: 99%
“…Adenotonsillar hypertrophy and fat deposition in the lateral fat pads, uvula, and tongue are contributing anatomic factors to airway narrowing that can cause OSA. Obesity is an independent risk factor for OSA in children after controlling for adenotonsillar hypertrophy [ 12 , 26 ]. It is possible that the same mechanism involving a diet high in saturated fatty acids that increase neutrophil recruitment within the airway inflammation and increase macrophage activation can explain the same effect not only in the lower but also in the upper airway causing OSA in obese patients [ 23 ].…”
Section: Common Risk Factorsmentioning
confidence: 99%